KOLABORASI MENULIS KREATIF BUKU BACAAN ANAK DALAM MENGEMBANGKAN INDUSTRI KREATIF PADA KOMUNITAS LITERASI WADAS KELIR PURWOKERTO - Kurniawan, Heru; Supriyono, Supriyono (Universitas Andalas, 2020)
In this era, writing is not enough to be done expressively with personal spontaneity, but need to be done collaboratively by considering aspects of the desired goals. One of them is when writing is done to fulfill economic goals as the basis of a community's creative industry. With the concept of a creative industry whose estuary is to produce economic products made from creative ideas, writing in Wadas Kelir Literacy Community (KLWK) is carried out with a planned collaborative working model based on creative industry standards of economic value. From here, the results of research that have been carried out are: first, writing collaboration begins with market research studies in an effort to identify trends in children's books that are being sought after by publishers and readers. Second, the formulation of themes and ideas is carried out in the discussion space and cooperation for the division of writing work. Third, the results of the writing work are reviewed and edited by a team of experts to identify the strengths and the weaknesses. Fourth, the book manuscript offer to publishers is carried out by a separate management who continues to carry out partnership work with publishers. Fifth, involved in efforts to distribute book sales through online stores that create trust in the community of publishers.